Building a winning team : technical leadership capabilities - Sutton, Brian (Systems management professor); Chatham, Robina (BCS Learning & Development, 2017)
The development of technical leadership capabilities is often overlooked as a training requirement in organisations but skills such as critical thinking and knowing when and how to exert your influence are key to business success. In this book management experts Brian Sutton and Robina Chatham describe and explain five management techniques to help you develop your leadership capabilities and build a winning team. With real life examples, tips and mini exercises, you'll also boost your soft skills as you steer your team to success.